2017
DOI: 10.4081/aiua.2017.4.259
|View full text |Cite
|
Sign up to set email alerts
|

The association between prostatitis and prostate cancer. Systematic review and meta-analysis

Abstract: Meta-analysis of 15 case-control studies shows that a history of clinical chronic prostatitis can significantly increase the odds for prostate cancer in the general population, whereas such association in African-American individuals remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 32 publications
2
37
1
1
Order By: Relevance
“…program and induction of pluripotency, as would occur in noncancerous cells to promote wound healing and maintain tissue homeostasis 15,16,66 . Viewed in this way and given the association of prostatitis with EMT 67,68 and prostate cancer 69 , prolonged activation of MUC1-C in settings of chronic inflammation and, in turn, the induction of stemness and reprogramming could hold important implications for PC progression and treatment. In this respect and of potential clinical relevance, targeting MUC1-C in PC cells with the GO-203 inhibitor, which blocks MUC1-C homodimerization and nuclear localization [42][43][44] , phenocopied the effects of MUC1-C silencing, including downregulation of (i) MYC→BRN2 signaling, (ii) MYCN, EZH2 and NE markers, and (iii) the OSKM pluripotency factors.…”
Section: Discussionmentioning
confidence: 99%
“…program and induction of pluripotency, as would occur in noncancerous cells to promote wound healing and maintain tissue homeostasis 15,16,66 . Viewed in this way and given the association of prostatitis with EMT 67,68 and prostate cancer 69 , prolonged activation of MUC1-C in settings of chronic inflammation and, in turn, the induction of stemness and reprogramming could hold important implications for PC progression and treatment. In this respect and of potential clinical relevance, targeting MUC1-C in PC cells with the GO-203 inhibitor, which blocks MUC1-C homodimerization and nuclear localization [42][43][44] , phenocopied the effects of MUC1-C silencing, including downregulation of (i) MYC→BRN2 signaling, (ii) MYCN, EZH2 and NE markers, and (iii) the OSKM pluripotency factors.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, meta-analyses of these studies have observed strong positive associations between clinical prostatitis and prostate cancer, supporting a role for prostate inflammation in prostate cancer development. [5][6][7][8] . However, none of these meta-analyses took into consideration the potential for detection bias in their pooled estimates.…”
Section: Introductionmentioning
confidence: 99%
“…13 Whether clinical prostatitis is a prostate cancer risk factor is unclear. [14][15][16] In our recent study, we found clinical prostatitis was associated with a lower prostate cancer risk in African American men. 17 Evidence also exists of unequal PSA amounts between white and African American men with prostate cancer.…”
Section: Introductionmentioning
confidence: 85%